(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Penobscot Field is located in the Sable Sub-basin, in the Nova Scotia Basin, belonging to the Canadian territory, and for the year of 1991, a 3D seismic acquisition was carried out in this region. Also, two exploratory wells were previously drilled (L-30 and B-41). Then, with the subsequent interpretation of the area, a discrepancy was found around 10ms to 15ms (approximately 25m) in the travel times of the seismic waves in the vicinity of well B-41, resulting in a false structural high in the Mississauga Formation and Naskapi Member. It is possibly caused by changes in geological facies and thickness of the Wyandot formation, consequently, B-41 well became dry. For these reasons, to identify the possible problem which caused everything mentioned above, the area between the wells was delimited by a seismic subvolume (by reducing the seismic cube), making a seismic interpretation of the top of the formations of interest, as well as an analysis of certain petrophysical properties in the wells, in order to delimit the thickness of the anomaly and, consecutively, the use of the seismic attributes for lateral identification of the anomaly in the Wyandot Formation.